IMPACT OF HYPEREMESIS GRAVIDARUM ON PREGNANCY OUTCOMES - Solechah, Mutiara; Kartini, Farida (Jurnal Kesehatan - STIKes Prima Nusantara, 2020)
Introduction: Hyperemesis gravidarum (HEG) or continuous nausea and vomiting can result in loss or even death in the mother and fetus. For most women who recover from HEG well, there is clear evidence of an increased risk of pregnancy outcomes.Purpose: The purpose of this scoping review is to map the evidence and conclude the literature about the effects of Hypermesis Gravidarum on pregnancy outcomes.Methods: In this scoping review, we evaluate the emerging evidence that HEG impacts pregnancy outcomes, by using two databases (Pubmed and ScienceDirect).Results: some of the effects of HCG, namely: LBW and Premature, Repetition of hyperemesis gravidarum across generations, Reduction of insulin sensitivity in children in childhood, Risk of placental abruption and increased risk of birth for small for gestational age (SGA), Provides a protective effect on the risk of cleft lip in new babies birth, Delayed nerve development in children, increased blood pressure and abnormal fetal brain development.Conclusion: HEG has an adverse risk to the outcome of pregnancy and can have an impact on the fetus, childhood and adulthood.